Addition of gadolinium contrast to three-dimensional SSFP MR sequences improves the visibility of coronary artery anatomy in young children - Shen, Quanli; Lin, Chengxiang; Yao, Qiong; Wang, Junbo; Zhou, Jian; He, Lan; Chen, Gang; Hu, Xihong (Frontiers in Pediatrics, 2023)
Objective: To compare the value of a gadolinium contrast-enhanced 1.5-T three-dimensional (3D) steady-state free precession (SSFP) sequence with a non-contrast 3D SSFP sequence for magnetic resonance coronary angiography (MRCA) in pediatric population. Materials and methods: Seventy-nine patients from 1 month to 18 years old were participated in this study. A 3D SSFP coronary MRA at 1.5-T was applied before and after Gadolinium-DTPA injection. The detection rates of coronary arteries and side branches were assessed by McNemar’s χ2 test. The image quality, vessel length, signal-to noise ratio (SNR) and contrast-to-noise ratio (CNR) of the coronary arteries were analyzed by Wilcoxon signed-rank test. The intra- and inter-observer agreements were evaluated with weighted kappa test or intraclass correlation efficient test. Results: Contrast-enhanced scan detected more coronary arteries compared with non-contrast enhanced scan in patients under two years old (P < 0.05). SSFP sequence with contrast media detected more coronary artery side branches in patients younger than 5 years (P < 0.05). The image quality of all the coronary arteries was better after the injection of Gadolinium-DTPA in children younger than 2 years (P < 0.05), but not significantly improved in children older than 2 years (P > 0.05). Contrast-enhanced 3D SSFP protocol detected longer length for the left anterior descending coronary artery in children younger than 2 years and the left circumflex coronary artery (LCX) in children younger than 5 years (P < 0.05). SNR and CNR of all the coronary arteries in children younger than 5 years, and the LCX and right coronary artery in children older than 5 years enhanced after injection of Gadolinium-DTPA (P < 0.05). The intra- and inter-observer agreements were high (0.803~0.998) for image quality, length, SNR and CNR of the coronary arteries in both pre- and post-contrast groups. Conclusion: The use of gadolinium-contrast in combination with the 3D SSFP sequence is necessary for coronary imaging in children under 2 years of age and may be helpful in children between 2 and 5 years. Coronary artery visualization is not significantly improved in children older than 5 years.